PENGEMBANGAN APLIKASI “PERANTARA” BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN IPS PADA MATERI INDONESIAKU KAYA BUDAYA KELAS IV - Lestari, Liza Rahma; Nurdinah Hanifah; Kusman Rukmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In social studies education, it is expected that future generations will understand cultural diversity with responsibility and concern for global issues, in line with their educational level and maturity. However, there is a gap between expectations and reality, particularly in the material